2013
DOI: 10.1016/j.cyto.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold fibroblasts immunoregulate activated macrophage phenotype

Abstract: Recent evidence suggests that fibroblasts play a critical role in regulating inflammation during wound healing because they express several inflammatory mediators in response to bacteria. The objective of this study was to analyze the effects of lipopolysaccaride (LPS) on the immunomodulatory properties of vocal fold fibroblasts (VFF) derived from polyps, scar and normal tissue co-cultured with macrophages, to provide insight into their interactions during the inflammatory process. Fibroblasts were co-cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
3
48
1
1
Order By: Relevance
“…8, 13 Specific to the larynx, other investigators have demonstrated that AAM and fibroblast interaction promotes inflammation associated with vocal fold scarring. 6 …”
Section: Introductionmentioning
confidence: 99%
“…8, 13 Specific to the larynx, other investigators have demonstrated that AAM and fibroblast interaction promotes inflammation associated with vocal fold scarring. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Our results have clarified the distributional and phenotypic changes in macrophages in injured murine vocal folds. The interaction between vocal fold fibroblasts and macrophages was reported in in vitro conditions 26 ; further investigation about the function of macrophages is warranted for a better understanding of wound healing in vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…VFFs produce several inflammatory mediators and play a role in regulating abnormal inflammatory responses by suppressing proinflammatory cytokines and neutrophil recruitment, and interfering with macrophage activation . As mentioned above, VFFs meet the criteria of mesenchymal stem cells, which have immunosuppressive properties, including inhibition of monocyte differentiation, T and B lymphocyte proliferation, and NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…VFFs produce several inflammatory mediators 16,21,53 and play a role in regulating abnormal inflammatory responses by suppressing proinflammatory cytokines and neutrophil recruitment, and interfering with macrophage activation. 16,54 As mentioned above, VFFs meet the criteria of mesenchymal stem cells, which have immunosuppressive properties, including inhibition of monocyte differentiation, T and B lymphocyte proliferation, and NK cell function. Thus, it has been demonstrated that VFFs may regulate the immunophenotype of macrophages, which acquire an anti-inflammatory profile based on low CD16, high CD206, and low human leukocyte antigen-DR expression.…”
Section: Discussionmentioning
confidence: 99%